Analisis Literatur Efektivitas Sistem Manajemen K3 di Perusahaan Kecil dan Menengah (UKM) - Alditia AlfaReza; Susilawati Susilawati (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Occupational Health and Safety (K3) is a crucial element in ensuring worker welfare and the smooth running of company operations. Even though SMEs (Small and Medium Enterprises) play an important role in the economy, the work accident rate in this sector is still high compared to large companies. Limited resources and lack of management support are often the main obstacles in implementing an effective K3 management system. Objective: This literature study aims to analyze the effectiveness of the K3 management system in SMEs, identify the challenges faced, and provide recommendations for improving the implementation of K3 in this sector. Methodology: This study uses a literature study approach by collecting and analyzing various academic sources including journal articles, government reports and relevant books. The literature search focused on academic databases such as Google Scholar, ScienceDirect, and ProQuest, using keywords such as